Common and idiosyncratic components of Latin American business cycles connectedness - Luciano Campos; Jesús Ruíz (Journal of Applied Economics, 2022)
This paper investigates the evolution of business cycles synchronization in Latin America since the 1990s. To do so, a Vector Autoregressive model is fed, alternatively, with the countries' Industrial Production Indexes and with these series filtered by the US financial conditions index, which is considered a common component affecting business cycles in the region. Additionally, a Markov switching model is estimated to identify regional recessions. Our findings indicate that business cycles connectedness rise significantly during regional recessions and that the common factor plays an important role. The evidence supports the usefulness of policy coordination among Latin American economies to cushion the spillover effects of exogenous shocks, and helps to identify subgroups of countries for which such coordination is recommendable.
Keywords: 330; Connectedness indexes; Latin American business cycles; Markov switching models; policy coordination; vector autoregressive analysis